The Skills Stimulated by Integrating Contents of Production Management in Higher Education in Engineering by Adapting ‘The Paper Airplane Factory’ Game - Fontana, Marcele Elisa; Nepomuceno, Vilmar Santos; Almeida, Lucas Trajano de Freitas (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
The professional of the future needs to have a set of behavioral (soft) and technical (hard) skills, but traditional teaching prioritizes hard skills. This article sets out to promote the integration of production management subject content into higher education in the field of engineering by adapting the game called “The Paper Airplane Factory”, and understand which skills were stimulated by the game in the perception of the students involved. As result, the game was shown to be suitable for contributing towards developing the skills and competencies of future engineers, such as: (1) analytical thinking and innovation, (2) active learning and learning strategies, (3) critical thinking and analysis, (4) creativity, originality and initiative and (5) leadership and social influence, of which four are considered soft skills.